Information Acquisition in a Tax Compliance Game - Sansing, Richard C. (The Accounting Review, 1993)
[The Internal Revenue Service (IRS) relies increasingly on its ability to detect taxpayer noncompliance without engaging in a comprehensive individual audit. The IRS's compliance initiative, Compliance 2000, emphasizes the targeting of noncompliant taxpayers rather than relying on random audits to enforce the tax laws. For example, the IRS uses a model developed from the Taxpayer Compliance Measurement Program (TCMP) to help it choose which returns to audit. The treatment of losses from tax shelter partnerships presents a difficult compliance problem for the IRS. It is not evident from the face of either the partnership return or the partner's return whether the losses from the partnership can be legitimately deducted. A plausible audit strategy is for the IRS to develop models that can predict when an individual is improperly deducting a loss. The tax shelter disclosure rules in I.R.C. section 6111 and section 6112 provide information to the IRS that helps it detect taxpayers investing in abusive tax shelters. Previous work has modeled tax compliance as a game between a wealth-maximizing taxpayer and a tax enforcement agency trying to maximize government revenues, net of audit costs (Graetz et al. 1986; Reinganum and Wilde 1986; Beck and Jung 1989). In these papers, the IRS uses the taxpayer's declaration of income when it decides whether to audit that taxpayer. The purpose of this paper is to examine the effect of information that helps the IRS predict tax evasion on the strategic choices made by the taxpayer and the IRS. The information has a direct effect by giving the IRS information that can improve its audit decision. It also has an indirect effect by changing the taxpayer's incentives to engage in tax evasion, which in turn changes the IRS's incentives to audit taxpayers. The optimal level of information acquisition is also examined. The analysis yields four important results regarding the effect of information on tax compliance. First, it can induce an increase in tax evasion. Second, it has no effect on the expected level of gross government revenues. Third, it can increase expected audit costs. Fourth, the optimal level of investment in information acquisition does not vary monotonically with tax rates, penalty rates, audit costs, or the amount of loss deducted by the taxpayer.]